Molecular determinants of outcomes in meningiomas - Lynes, John; Flores-Milan, Gabriel; Rubino, Sebastian; Arrington, John; Macaulay, Robert; Liu, James K. C.; Beer-Furlan, Andre; Tran, Nam D.; Vogelbaum, Michael A.; Etame, Arnold B. (Frontiers in Oncology, 2022)
Meningiomas are the most common intracranial primary tumor in adults. Surgery is the predominant therapeutic modality for symptomatic meningiomas. Although the majority of meningiomas are benign, there exists a subset of meningiomas that are clinically aggressive. Recent advances genetics and epigenetics have uncovered molecular alterations that drive tumor meningioma biology with prognostic and therapeutic implications. In this review, we will discuss the advances on molecular determinants of therapeutic response in meningiomas to date and discuss findings of targeted therapies in meningiomas.